Antidepressants and the Risk of Fall-Related Injury in Older Adults with Incident Depression in the United States: A Comparative Safety Analysis - Ashley Tabah; Laura S. Gold; Zachary A. Marcum; Ryan N. Hansen (MDPI AG, 2023)
Though it is well documented that antidepressants are associated with an increased risk of falls in older adults at the drug class level, the comparative risk between individual antidepressants for fall injury in older adults with depression is unknown. Currently, clinicians are making decisions at the drug class level without consideration of the potential that there could be safer choices within classes. We compared the risk of fall injury among initiators of bupropion, duloxetine, fluoxetine, paroxetine, and venlafaxine to those of (es)citalopram and, separately, sertraline. We performed a retrospective cohort study using the MarketScan® Medicare Supplemental claims from 2007 to 2019. Individuals had incident depression (washout in previous continually enrolled year) with a first antidepressant claim up to three months after depression diagnosis. Individuals were followed for the first three months of antidepressant use until the first occurrence of fall injury, change/discontinuation of antidepressant, discontinued insurance coverage, or end of study. Propensity score inverse probability of treatment-weighted Cox proportional hazards models estimated hazard ratios (HRs) and 95% confidence intervals for each antidepressant comparison and fall injury. We identified 114,505 individuals (mean age 76.6 years, 68% female, 97% without prior fall). A higher risk of fall injury was associated with initiating bupropion (HR 1.20 to 1.61), duloxetine (HR 1.27 to 1.36), paroxetine (HR 1.14 to 1.22), and venlafaxine (HR 1.22 to 1.34) when compared to (es)citalopram or sertraline. New use of duloxetine, bupropion, paroxetine, and venlafaxine was associated with a higher risk of fall injury compared to (es)citalopram and sertraline.